1993
DOI: 10.1063/1.464384
|View full text |Cite
|
Sign up to set email alerts
|

Memory and temperature induced suppression of activated rate processes

Abstract: A detailed study of memory and temperature induced suppression of activated rate processes is presented. Numerical computations demonstrate that long memory in the presence of moderate barriers can induce noticeable deviation of the reaction rate constant from the predictions of the Kramers–Grote–Hynes theory. A canonical variational transition state theory, based on finding the optimized planar dividing surface, is shown to account quantitatively for the observed suppression of the rate. The suppression is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…38,39 In addition, augmented dynamical systems similar to the ones presented here have been used as the basis of formal analysis 40 and numerical algorithms for solving the GLE by computer simulation. 41,42 Our emphasis here is different: We interpret the GLE as a dynamical system and analyze its qualitative character in detail. The geometrical approach of qualitative dynamics yields useful additional physical insights into this general mathematical approach to non-Markovian systems.…”
Section: ͑4͒mentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 In addition, augmented dynamical systems similar to the ones presented here have been used as the basis of formal analysis 40 and numerical algorithms for solving the GLE by computer simulation. 41,42 Our emphasis here is different: We interpret the GLE as a dynamical system and analyze its qualitative character in detail. The geometrical approach of qualitative dynamics yields useful additional physical insights into this general mathematical approach to non-Markovian systems.…”
Section: ͑4͒mentioning
confidence: 99%
“…͑40͒ ͑when augmented by a random force͒ are commonly employed as the basis of a numerical method for solving the non-Markovian GLE with exponential memory. 41,42 FIG. 5.…”
Section: ͑41͒mentioning
confidence: 99%
“…The details of solution of the variational problem can be found elsewhere. [55][56][57] Some specific details are given in Appendix A. The result for the coefficients ͕a j ͖ is…”
Section: ͑38͒mentioning
confidence: 99%
“…Martens [33], following earlier approaches [30,31,32], suggested a construction of the dynamical phase space under the assumption that the friction kernel γ(t) satisfies a linear differential equation with constant coefficients of the form…”
Section: The Extended Phase Spacementioning
confidence: 99%
“…Several constructions of appropriate phase spaces have been suggested in the literature, e.g. in [30,31,32,33]. It will here be shown that the phase space depends critically on the way in which the system is prepared.…”
Section: Introductionmentioning
confidence: 99%